Isolation and Characterization of Microsatellite Markers in Canthon (Petelcanthon) Staigi (Coleoptera: Scarabaeidae) and Cross-Amplifi cation in Related Species - GAS Cruz; CA Ferreira-Neto; AC Lira-Neto; RC Moura (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2017)
The species Canthon (Peltecanthon) staigi is a Neotropical "dung beetle" from Brazilian Atlantic Rainforest, which plays a key ecological role reallocating organic material and in some cases being a seed disperser. Moreover, this species is considered a bio indicator once is sensible to environment changes like the habitat loss. Despite its' ecological importance nothing is known regarding the population structure of this dung beetle species. Molecular markers are informative tools to evaluate the extent and distribution of genetic diversity of the C. (P.) staigi populations remaining. Here we report the isolation and characterization of the first microsatellite markers for C. (P.) staigi. Four polymorphic microsatellite loci were  characterized with allele numbers ranging from four to five per locus. The observed and expected heterozygosis ranged from 0.466 to 0.516 and 0.485 to 0.623, respectively. All loci were observed on Hardy Weinberg equilibrium. Linkage disequilibrium was not detected in any loci. From a subset of 24 loci it was observed positive transferability of six loci on four different tribes of Scarabaeidae. The loci will be used for studying population genetic structure of C. (P.) staigi and the cross-species amplification success extends the utility of these markers to be applied also on related species.